49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3853
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Single Injector with Applied High Frequency Pressure Disturbances For Applications To Liquid Rocket Engine Combustion Instabilities

Abstract: This research investigation demonstrates a new high frequency combustion instability control approach in which the dominant instability mode is able to be suppressed by strategically applying pressure disturbances within the oxidizer post of an injector. By housing a piezoelectric speaker at the base of the injector, the incoming oxidizer flow into the combustor is able to be acoustically modulated, causing the oscillatory behavior of the combustor to be altered. Thus, given the correct acoustic signal, a supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This high frequency instability control technique was based off the fast response actuation valve study, with the thought that modulating the oxidizer flow acoustically at multiple frequencies (i.e. applying band-limited white noise) instead of a single frequency could lead to a more reliable instability suppression [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high frequency instability control technique was based off the fast response actuation valve study, with the thought that modulating the oxidizer flow acoustically at multiple frequencies (i.e. applying band-limited white noise) instead of a single frequency could lead to a more reliable instability suppression [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Further testing with varying amplitudes of single frequency acoustic modulation is proposed to investigate repeatability of the results of this study. 5. Upon comparing both the band-limited white noise and single frequency sweep studies, it was found that the band-limited white noise approach more reliably suppressed the instability across the frequency range than single frequency acoustic modulation, as there were certain frequencies in which a 70+ % instability reduction was not met for the highest RMS % frequency sweep test.…”
mentioning
confidence: 97%
“…These mechanisms have been integrated into both gas turbine and rocket combustors with open loop control configurations resulting in a significant reduction in combustion instability at certain modulation frequencies. [9][10][11][12][13] Similar performance can be achieved through the use of fluidic oscillators as their oscillation frequency provides steady propellant modulation in open loop control without the need for speakers and high speed valves. A previous experiment saw up to a 40% reduction in combustion instability pressure oscillations when modulating the fuel flow with a fluidic oscillator in a bluff body combustor.…”
Section: Introductionmentioning
confidence: 95%
“…2,3,[18][19][20] While passive techniques are limited in their effectiveness over a range of combustor operating conditions, they are attractive due to their simplicity and reliability. 21 Looking closer at propellant modulation studies, [22][23][24][25][26][27][28][29] the modulation methods, propellants, and injectors vary, but all the studies see a reduction in combustion instabilities due to the oscillatory propellant flow decoupling the pressure oscillations and heat release. Fluidic oscillators use internal fluid dynamics to create an oscillatory outlet jet and require no moving parts, making them an ideal candidate to replicate propellant flow modulation without the power consumption and reliability concerns associated with high speed valving and acoustic modulation.…”
Section: Introductionmentioning
confidence: 99%